Behavior analysis for effective teaching - Vargas, Julie S. (New York, NY : Routledge, 2020)
"Behavior Analysis for Effective Teaching is a clearly written book on the integration of non-aversive behavior analysis principles into classrooms and other school settings. Carefully revised and updated throughout, this third edition includes new content on precision teaching and a new chapter on how teachers can provide appropriate education for students with special disabilities who are included in their classrooms. The volume focuses on merging behavior management with effective student instruction illustrated with examples from real teachers' experiences. The book is a perfect primary resource for undergraduate and graduate courses in teacher education, special education, school psychology, and school counseling, as well as for preparation toward the BACB Credentialing Exam"--
Includes bibliographical references and index.
PBK.
Keywords: Behavioral assessment of children; Problem children -- Education; Effective teaching